ANALYSIS OF DOUBLE RESISTANCE SPOT WELDING'S FAILURE IN HIGH STRENGTH LOW ALLOY STEEL - Al-Bayati, Hayder; Mahmood, Ibtihal A.; Khoshnaw, Fuad (Journal of Applied Engineering Science, 2023)
High strength low alloy steel (HSLA DOCOL 500 LA) is utilized in the automotive structure because of its superior qualities such as good fatigue resistance, a high strength-to-weight ratio, assisting in reducing the weight of the vehicle, increasing fuel efficiency and lower CO2 emissions. Resistance Spot Welding (RSW) is the most welding technique that is used to join automobile parts together. This study investigated the RSW process for high-strength steel. By utilizing the Taguchi approach, the optimization process for double spot nuggets with the principal welding parameters of welding current, welding time, and electrode force was carried out. The values of optimum parameters were 8800Amp for welding current, welding time of 30 cycles and 2560 N for electrode force. Mechanical and microstructure tests were carried out to study the failure modes while the fatigue test was achieved to obtain the fatigue endurance limit and it was at a maximum load 1500 N and during the fatigue test two types of failure happened: full pull-out failure and cracks around the nugget zone.
Keywords: high strength low alloy steel (HSLA), resistance spot welding, taguchi method, fatigue life, microhardness